2017
DOI: 10.1080/00325481.2017.1281083
|View full text |Cite
|
Sign up to set email alerts
|

The evolving role of oral hormonal therapies and review of conjugated estrogens/bazedoxifene for the management of menopausal symptoms

Abstract: This review describes the evolving role of oral hormone therapy (HT) for treating menopausal symptoms and preventing osteoporosis, focusing on conjugated estrogens/bazedoxifene (CE/BZA). Estrogens alleviate hot flushes and prevent bone loss associated with menopause. In nonhysterectomized women, a progestin should be added to estrogens to reduce the risk of endometrial cancer. Use of HT declined since the Women's Health Initiative (WHI) studies showed that HT does not prevent coronary heart disease (CHD) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 92 publications
0
22
0
Order By: Relevance
“…The FDA-approved drug bazedoxifene, known as a selective estrogen modulator, is currently used for the postmenopausal osteoporosis [23]. Recently, using multiple-ligand simultaneous docking and drug repositioning, we identified bazedoxifene as a novel small-molecule inhibitor of GP130 [24].…”
Section: Introductionmentioning
confidence: 99%
“…The FDA-approved drug bazedoxifene, known as a selective estrogen modulator, is currently used for the postmenopausal osteoporosis [23]. Recently, using multiple-ligand simultaneous docking and drug repositioning, we identified bazedoxifene as a novel small-molecule inhibitor of GP130 [24].…”
Section: Introductionmentioning
confidence: 99%
“…CE/BZA has been studied in five RCTs involving more than 7500 women and no increase in endometrial hyperplasia was found. It may be an option for women who poorly tolerate the side effects of progestins [ 45 •].…”
Section: Prevention In the General Populationmentioning
confidence: 99%
“…These may be due to absorption of exogenous hormone, obesity, late menopause, high pressure, etc [ 3 ]. Patients are generally treated with surgery [ 4 ], and in some cases, a combination of chemotherapy, radiotherapy, and hormone therapy [ 5 ]. The five-year survival rate in patients was only approximately 80%, while about 15-20% develop metastasis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%